Na expressão M = | x – 1 | + | x – 3 |, supondo 1 ≤ x ≤ 3, podemos afirmar que:
A. M = 2
B. M = 3
C. M = 4
D. M = 5
E. M = 6
Sasuke322:
oi
Respostas
respondido por:
0
Resposta:
eu vou entar no google ai eu vou respomder ta
respondido por:
2
Explicação passo-a-passo:
Na expressão M = | x – 1 | + | x – 3 |, supondo 1 ≤ x ≤ 3, podemos afirmar que:
A. M = 2
B. M = 3
C. M = 4
D. M = 5
E. M = 6
Resposta:
C
Perguntas similares
4 anos atrás
4 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás